2004
DOI: 10.21273/jashs.129.4.0553
|View full text |Cite
|
Sign up to set email alerts
|

ISSR and AFLP Markers Differ among American Watermelon Cultivars with Limited Genetic Diversity

Abstract: Wide phenotypic diversity exists among American heirloom cultivars of watermelon (Citrullus lanatus var. lanatus). However, in published studies, low or no polymorphism was revealed among those heirlooms using isozyme or randomly amplified polymorphic DNA (RAPD) markers. In this study, experiments with inter-simple sequence repeat (ISSR) [also known as simple sequence repeat-(SSR-) anchored primers] and amplified fragment-length polymorphism (AFLP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 18 publications
5
48
0
1
Order By: Relevance
“…The methylated bands that are polymorphic (MP) were used to construct Neighbor-Joining (NJ) phenograms to explore whether the patterns of genetic relationships were consistent with those determined previously (Levi et al 2004). The first and the second analyses included specific MPs of MspI and HpaII, respectively, to compare the tree topologies of complete methylation (MspI) versus hemi-methylation (HpaII).…”
Section: Methylation Profiles In Watermelon Heirloomsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methylated bands that are polymorphic (MP) were used to construct Neighbor-Joining (NJ) phenograms to explore whether the patterns of genetic relationships were consistent with those determined previously (Levi et al 2004). The first and the second analyses included specific MPs of MspI and HpaII, respectively, to compare the tree topologies of complete methylation (MspI) versus hemi-methylation (HpaII).…”
Section: Methylation Profiles In Watermelon Heirloomsmentioning
confidence: 99%
“…There is wide phenotypic diversity in terms of growth habits, fruit traits and resistance to biotic and abiotic stress (Levi et al 2004). After using wide ranging DNA marker tools, Levi et al (2001Levi et al ( , 2004, concluded that there is a very narrow genetic diversity at the DNA sequence level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, of 1,309 RAPD markers, only 75 were polymorphic (5.9%) between two watermelon breeding lines (Harris et al 2008). Other marker systems such as AFLP (Che et al 2003;Levi et al 2004), SRAP (Levi et al 2006;Zhang et al 2008), EST-PCR (Levi et al 2009) and HFO-TAG produced slightly higher polymorphism among watermelon cultivars than the RAPD markers, but all in general were not breeder friendly. Results from these genetic assays were hardly comparable due to lack of a common core set of reference genotypes and the use of different marker systems.…”
Section: Introductionmentioning
confidence: 99%